Surface treated steel plate
By forming an F-Mg concentrated layer at the coating interface of the zinc-based plating layer, the problem of difficulty in suppressing white rust in the flowing water or condensing environment in the prior art is solved, and high white rust resistance and black degeneration resistance in these environments are achieved.
Patent Information
- Application Number
- CN202280092836.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-03
- Filing Date
- 2022-09-28
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2042-09-28
AI Technical Summary
The prior art is difficult to effectively suppress the generation of white rust in an environment in which contacts flowing water or condensation occurs under a chemical conversion coating formed on the surface of a zinc-based plating layer.
The F and Mg concentrated layers are formed in the area of the chemical conversion coating that is in contact with the interface of the coating layer, and in particular, the F-Mg concentrated layers with Mg concentration of more than 1.50% and less than 40.00%, and F concentration of more than 0.50% and less than 5.00%, thereby improving white rust resistance.
In an environment where the flowing water is in contact or condensation occurs, the white rust generation is significantly suppressed, and the white rust resistance is improved, while ensuring that the blackening resistance is not deteriorated.
Smart Images

Figure CN118786244B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a surface treated steel plate.
[0002] This application claims priority based on Japanese Patent Application No. 2022-032606 filed in Japan on March 3, 2022, the contents of which are incorporated herein by reference. Background Art
[0003] Conventionally, plated steel sheets (zinc-plated steel sheets) having a zinc-based plating layer formed on the surface of the steel sheet have been used in a wide range of applications such as automobiles, building materials, and home appliances. Among them, Mg-containing zinc-plated steel sheets containing 0.5 mass % or more of Mg have high corrosion resistance due to the effect of Mg, and are therefore used in applications such as building materials that require particularly strict corrosion resistance.
[0004] In such applications, the surface of the zinc-plated steel sheet is subjected to a chromium-free chemical conversion treatment, for example, a chemical conversion treatment mainly using an organic silicon compound having a cyclic siloxane bond, for the purpose of improving white rust resistance.
[0005] For example, Patent Document 1 discloses a surface-treated steel material, wherein a composite film containing various components is formed by (1) applying a water-based metal surface treatment agent on the surface of the steel material and drying the water-based metal surface treatment agent, wherein the water-based metal surface treatment agent comprises (2) an organic silicon compound (W), (3) at least one fluorine compound (X) selected from fluorotitanic acid or fluorozirconic acid, (4) phosphoric acid (Y) and (5) a vanadium compound (Z), wherein the organic silicon compound (W) is obtained by mixing a silane coupling agent (A) containing one amino group in the molecule and a silane coupling agent (B) containing one glycidyl group in the molecule at a solid content mass ratio [(A) / (B)] of 0.5 to 1.7, and wherein the organic silicon compound (W) contains two or more groups of the formula -SiR 1 R 2 R 3 (Where R 1 , R 2 and R 3(a) and at least one hydrophilic functional group (b) selected from the group consisting of a hydroxyl group (another hydroxyl group different from the hydroxyl group that can be contained in the functional group (a)) and an amino group, and the average molecular weight is 1000 to 10000, and in the components of the composite film, the solid content mass ratio of the (6) organic silicon compound (W) to the fluorine compound (X) is (X) / (W )〕is 0.02 to 0.07, (7) the solid content mass ratio of the organosilicon compound (W) to the phosphoric acid (Y)〔(Y) / (W)〕is 0.03 to 0.12, (8) the solid content mass ratio of the organosilicon compound (W) to the vanadium compound (Z)〔(Z) / (W)〕is 0.05 to 0.17, and (9) the solid content mass ratio of the fluorine compound (X) to the vanadium compound (Z)〔(Z) / (X)〕is 1.3 to 6.0.
[0006] According to Patent Document 1, it is disclosed that the surface treated steel material satisfies all of corrosion resistance, heat resistance, fingerprint resistance, electrical conductivity, paintability, and black dross resistance during processing.
[0007] In addition, Patent Document 2 discloses a hot-dip galvanized alloy steel sheet with excellent corrosion resistance, wherein a chemical conversion film having one or more of the hydroxides, oxides, oxyacids, oxyacids, and fluorides of valve metals as main components is formed on a Mg-containing zinc alloy coating via an interfacial reaction layer comprising one or more of a composite compound selected from magnesium fluoride, magnesium phosphate, and magnesium and valve metal oxyacids.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent No. 4776458
[0011] Patent Document 2: Japanese Patent Application Publication No. 2007-23309 Summary of the invention
[0012] Problems to be solved by the invention
[0013] Even when the chemical conversion coating described in Patent Documents 1 and 2 is formed on the surface of the zinc-based plating layer, a certain effect of improving white rust resistance can be obtained. However, the inventors' research results have revealed that, with such chemical conversion treatment, when steel materials are placed in an environment such as contact with running water or an environment such as an environment where condensation occurs, for example, in civil engineering and construction applications, white rust may be generated at an early stage.
[0014] That is, the present invention is based on the premise that general properties such as blackening resistance are not deteriorated, and an object is to provide a surface-treated steel sheet capable of suppressing the generation of white rust in both an environment such as contact with running water and an environment such as an environment where condensation occurs.
[0015] Means for solving problems
[0016] The present inventors have studied methods for suppressing the generation of white rust in an environment such as contact with running water and an environment such as condensation, based on a Mg-containing zinc-plated steel sheet subjected to a chemical conversion treatment mainly using an organic silicon compound. As a result, they have found that the white rust resistance in an environment such as contact with running water (running water environment) can be improved, particularly, by forming a layer in which F and Mg are concentrated in a region of the chemical conversion film in contact with the interface between the plating layer and the chemical conversion film.
[0017] Furthermore, as a result of further studies, it was found that white rust resistance is improved even in an environment where condensation occurs (condensation environment) by forming a layer where F and Mg are concentrated near the interface and reducing the F concentration in regions other than the layer where F and Mg are concentrated.
[0018] The present invention has been made based on the above findings. The gist of the present invention is as follows.
[0019] [1] A surface-treated steel sheet according to one embodiment of the present invention comprises a base steel sheet, a coating formed on the base steel sheet, and a chemical conversion coating formed on the coating, wherein the coating contains 50 mass % or more of Zn and 0.3 mass % or more of Mg, the chemical conversion coating contains a silicon compound, P and F, and Mg, the average Si concentration of the chemical conversion coating is 10 mass % or more, the chemical conversion coating has an F-Mg concentrated layer in a region in contact with an interface between the chemical conversion coating and the coating, the F-Mg concentrated layer has an Mg concentration of 1.50 mass % or more and 40.00 mass % or less, and an F concentration of 0.50 mass % or more and 5.00 mass % or less, the F-Mg concentrated layer has a thickness of 1.0 nm or more, and in a region of the chemical conversion coating other than the F-Mg concentrated layer, the average Mg concentration is less than 0.50 mass %, and the average F concentration is less than 0.50 mass %.
[0020] [2] The surface-treated steel sheet according to [1], wherein in the chemical conversion coating, the thickness of the F-Mg concentrated layer may be 5.0 nm or more and 100.0 nm or less.
[0021] [3] The surface-treated steel sheet according to [1] or [2], wherein the chemical composition of the coating layer may be, in mass %, Al: 4.0% to 25.0%, Mg: 0.3% to 12.5%, Sn: 0% to 20%, Bi: 0% to 5.0%, In: 0% to 2.0%, Ca: 0% to 3.0%, Y: 0% to 0.5%, La: 0% to 0.5%, Ce: 0% to 0.5%, Si: 0% to 2.5%, Cr: 0% to 3.0%, Less than 0.25%, Ti: 0% or more and less than 0.25%, Ni: 0% or more and less than 0.25%, Co: 0% or more and less than 0.25%, V: 0% or more and less than 0.25%, Nb: 0% or more and less than 0.25%, Cu: 0% or more and less than 0.25%, Mn: 0% or more and less than 0.25%, Fe: 0% or more and less than 5.0%, Sr: 0% or more and less than 0.5%, Sb: 0% or more and less than 0.5%, Pb: 0% or more and less than 0.5%, B: 0% or more and less than 0.5%, and the remainder: Zn and impurities.
[0022] Effects of the Invention
[0023] According to the above aspect of the present invention, it is possible to provide a surface-treated steel sheet capable of suppressing the generation of white rust in any of an environment such as contact with running water and an environment such as generation of condensation. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram showing an example of a cross section of a surface-treated steel sheet according to the present embodiment. DETAILED DESCRIPTION
[0025] Hereinafter, a surface-treated steel sheet according to an embodiment of the present invention (surface-treated steel sheet according to the present embodiment) will be described.
[0026] The surface treated steel plate 1 of this embodiment is as follows Figure 1 As shown in FIG. 1 , the substrate has a base steel plate 11, a plating layer 12 formed on the base steel plate 11, and a chemical conversion coating 13 formed on the plating layer 12. In addition, the chemical conversion coating 13 has an F-Mg concentrated layer 14 in a region in contact with the interface between the chemical conversion coating 13 and the plating layer 12.
[0027] exist Figure 1 In the embodiment, the plating layer 12 and the chemical conversion coating (sometimes simply referred to as a coating) 13 are formed on only one surface of the base steel plate 11, but may be formed on both surfaces.
[0028] Hereinafter, the base steel plate 11 , the plating layer 12 , and the chemical conversion treatment film 13 will be described respectively.
[0029] <Base Steel Plate>
[0030] The surface treated steel plate 1 of this embodiment can obtain excellent corrosion resistance by the coating 12 and the chemical conversion film 13. The base steel plate 11 is a steel material without the coating 12 or the chemical conversion film 13 on its surface, and its material (strength, etc.), plate thickness, etc. are not particularly limited. The base steel plate 11 can be determined according to the applicable product, the required strength, plate thickness, etc. For example, a hot-rolled mild steel plate or hot-rolled steel plate described in JIS G3131: 2018 or JIS G3113: 2018, or a cold-rolled steel plate described in JIS G3141: 2017 can be used.
[0031] <Plating>
[0032] The coating 12 of the surface treated steel plate 1 of the present embodiment is a coating (zinc coating) formed on the surface of the base steel plate 11, with Zn (zinc) as the main component and containing 0.3% by mass or more of Mg. Among them, the so-called Zn as the main component means that the Zn concentration (content) is 50% by mass or more. The Zn concentration (content) can also be set to 55% by mass or more, 60% by mass or more, 65% by mass or more, 70% by mass or more, 75% by mass or more, or 80% by mass or more. The Zn concentration (content) is 99.7% by mass or less, but can also be set to 95.7% by mass or less, 95% by mass or less, 92% by mass or less, 90% by mass or less, or 86% by mass or less.
[0033] Mg is an element necessary for forming an F-Mg concentrated layer on the chemical conversion film after the chemical conversion treatment. When the Mg concentration (content) is less than 0.3 mass %, the F-Mg concentrated layer is not formed. Therefore, the Mg concentration is set to 0.3 mass % or more.
[0034] In the plating layer 12, the concentration (content) of the elements other than the above is not limited. However, the chemical composition of the plating layer is, in mass%, Al: 4.0% or more and less than 25.0%, Mg: 0.3% or more and less than 12.5%, Sn: 0% or more and less than 20%, Bi: 0% or more and less than 5.0%, In: 0% or more and less than 2.0%, Ca: 0% or more and less than 3.0%, Y: 0% or more and less than 0.5%, La: 0% or more and less than 0.5%, Ce: 0% or more and less than 0.5%, Si: 0% or more and less than 2.5%, Cr: 0% or more and less than 0.25%, Ti: 0% or more and less than 0.25%, N i: 0% to 0.25%, Co: 0% to 0.25%, V: 0% to 0.25%, Nb: 0% to 0.25%, Cu: 0% to 0.25%, Mn: 0% to 0.25%, Fe: 0% to 5.0%, Sr: 0% to 0.5%, Sb: 0% to 0.5%, Pb: 0% to 0.5%, B: 0% to 0.5%, and the remainder: Zn and impurities, thereby obtaining excellent corrosion resistance as a surface-treated steel sheet, which is therefore preferred.
[0035] The reasons for the preferred chemical composition of the plating layer 12 will be described. Unless otherwise specified, % of the concentration (content) of each element in the chemical composition of the plating layer is mass %.
[0036] [Al: 4.0% or more and less than 25.0%]
[0037] Al is an element effective for improving corrosion resistance in zinc-based plating. In order to fully obtain the above-mentioned effect, the Al concentration is preferably set to 4.0% or more. The Al concentration may also be set to 6.0% or more, 8.0% or more, 10.0% or more, or 13.0% or more.
[0038] On the other hand, if the Al concentration is 25.0% or more, the corrosion resistance of the cut end surface of the plating layer decreases. Therefore, the Al concentration is preferably less than 25.0%. The Al concentration may also be set to 23.0% or less, 20.0% or less, 18.0% or less, or 15.0% or less.
[0039] [Mg: 0.3% or more and less than 12.5%]
[0040] As described above, in order to form the F-Mg concentrated layer, the Mg concentration is 0.3% or more. Mg is also an element that has the effect of improving the corrosion resistance of the coating. In the case of obtaining the effect of improving the corrosion resistance, the Mg concentration is preferably set to 0.5% or more. The Mg concentration is more preferably 1.0% or more, and further preferably 2.0% or more or 3.0% or more. The Mg concentration can also be set to 4.0% or more, 5.0% or more, 6.0% or more, or 8.0% or more.
[0041] On the other hand, if the Mg concentration is 12.5% or more, the effect of improving corrosion resistance is saturated, and the workability of the coating layer is sometimes reduced. In addition, there are manufacturing problems such as an increase in the amount of dross generated in the coating bath. Therefore, it is preferable to set the Mg concentration to less than 12.5%. The Al concentration may also be set to 12.0% or less, 11.0% or less, 10.0% or less, or 9.0% or less.
[0042] The plating layer 12 may further contain the following elements as a chemical composition. The inclusion of the following elements is not essential, and the lower limit of these elements is 0%.
[0043] [Sn: 0% or more and 20% or less]
[0044] [Bi: 0% or more and less than 5.0%]
[0045] [In: 0% or more and less than 2.0%]
[0046] These elements contribute to the improvement of corrosion resistance and chemical corrosion resistance. Therefore, one or more of these elements may be contained. In order to obtain the above-mentioned effects, the concentration of each element is preferably set to 0.05% or more.
[0047] Among them, Sn is preferred because it is a low melting point metal and can be easily contained without impairing the properties of the plating bath.
[0048] On the other hand, if the Sn concentration exceeds 20%, the Bi concentration is 5.0% or more, or the In concentration is 2.0% or more, the corrosion resistance decreases. Therefore, it is preferred to set the Sn concentration to 20% or less, the Bi concentration to less than 5.0%, and the In concentration to less than 2.0%, respectively. The Sn concentration may also be set to 15.0% or less, 10.0% or less, 5.0% or less, or 3.0% or less. The Bi concentration may also be set to 4.0% or less, 3.0% or less, 2.0% or less, or 1.0% or less. The In concentration may also be set to 1.5% or less, 1.0% or less, or 0.5% or less.
[0049] [Ca: 0% or more and 3.0% or less]
[0050] Ca is an element that reduces the amount of dross that is easily formed during operation and contributes to the improvement of plating productivity. Therefore, Ca may be contained. In order to obtain this effect, the Ca concentration is preferably set to 0.1% or more.
[0051] On the other hand, if the Ca concentration is high, the corrosion resistance of the flat surface of the plating layer itself tends to deteriorate, and sometimes the corrosion resistance around the weld is also deteriorated. Therefore, the Ca concentration is preferably 3.0% or less. The Bi concentration can also be set to 2.0% or less, 1.0% or less, or 0.5% or less.
[0052] [Y: 0% or more and 0.5% or less]
[0053] [La: 0% or more and less than 0.5%]
[0054] [Ce: 0% or more and less than 0.5%]
[0055] Y, La, and Ce are elements that contribute to improvement of corrosion resistance. In order to obtain this effect, it is preferred that 0.05% or more of each of them is contained.
[0056] On the other hand, if the concentration of these elements becomes excessive, the viscosity of the coating bath increases in many cases, and the preparation of the coating bath itself becomes difficult, and there is a concern that a steel material with good coating properties cannot be produced. Therefore, it is preferred to set the Y concentration to 0.5% or less, the La concentration to less than 0.5%, and the Ce concentration to less than 0.5%. The concentrations of these elements may also be set to 0.3% or less, 0.2% or less, or 0.1% or less.
[0057] [Si: 0% or more and less than 2.5%]
[0058] Si is an element that contributes to the improvement of corrosion resistance. In addition, Si is also an element that has the following effects: when forming a coating on a steel sheet, it is possible to suppress the excessive thickness of the alloy layer formed between the steel sheet surface and the coating, thereby improving the adhesion between the steel sheet and the coating. In order to obtain these effects, it is preferred that the Si concentration be set to 0.1% or more. The Si concentration is more preferably 0.2% or more.
[0059] On the other hand, if the Si concentration is 2.5% or more, not only will excessive Si be precipitated in the coating, the corrosion resistance will be reduced, but also the processability of the coating will be reduced. Therefore, it is preferred to set the Si concentration to less than 2.5%. The Si concentration is more preferably 1.5% or less. The Si concentration may also be set to 1.2% or less, 1.0% or less, 0.6% or less, or 0.3% or less.
[0060] [Cr: 0% or more and less than 0.25%]
[0061] [Ti: 0% or more and less than 0.25%]
[0062] [Ni: 0% or more and less than 0.25%]
[0063] [Co: 0% or more and less than 0.25%]
[0064] [V: 0% or more and less than 0.25%]
[0065] [Nb: 0% or more and less than 0.25%]
[0066] [Cu: 0% or more and less than 0.25%]
[0067] [Mn: 0% or more and less than 0.25%]
[0068] These elements contribute to the improvement of corrosion resistance. In order to obtain this effect, it is preferable to set the concentration of one or more of these elements to 0.05% or more.
[0069] On the other hand, if the concentration of these elements becomes excessive, the viscosity of the coating bath increases in many cases, and the preparation of the coating bath itself becomes difficult, and there is a concern that a steel material with good coating properties cannot be produced. Therefore, it is preferred that the concentration of each element is set to less than 0.25%. The concentration of these elements may also be set to 0.20% or less, 0.10% or less, or 0.05% or less.
[0070] [Fe: 0% or more and 5.0% or less]
[0071] Fe is mixed into the coating as an impurity when the coating is manufactured. Although it may be contained up to about 5.0%, if it is within this range, the adverse effect on the effect of the surface treated steel sheet of this embodiment is small. Therefore, it is preferable to set the Fe concentration to 5.0% or less. The Fe concentration may also be set to 3.0% or less, 2.0% or less, 1.0% or less, or 0.5% or less.
[0072] [Sr: 0% or more and less than 0.5%]
[0073] [Sb: 0% or more and less than 0.5%]
[0074] [Pb: 0% or more and less than 0.5%]
[0075] If Sr, Sb, and Pb are contained in the plating layer, the appearance of the plating layer changes, zinc spangles are formed, and improvement of metallic luster is confirmed. In order to obtain this effect, it is preferred that the concentration of one or more of Sr, Sb, and Pb be set to 0.05% or more.
[0076] On the other hand, if the concentration of these elements becomes excessive, the viscosity of the coating bath increases in many cases, and the preparation of the coating bath itself becomes difficult, and there is a concern that a steel material with good coating properties cannot be produced. Therefore, it is preferred that the concentration of each element is set to less than 0.5%. The concentration of these elements may also be set to 0.4% or less, 0.2% or less, or 0.1% or less.
[0077] [B: 0% or more and less than 0.5%]
[0078] B is an element that, when contained in the plating layer, combines with Zn, Al, Mg, etc. to form various intermetallic compounds. The intermetallic compounds have the effect of improving LME crack resistance. In order to obtain this effect, the B concentration is preferably set to 0.05% or more.
[0079] On the other hand, if the B concentration becomes excessive, there is a concern that the melting point of the coating will rise significantly, the coating workability will deteriorate, and a surface-treated steel sheet with good coating properties cannot be obtained. Therefore, it is preferred that the B concentration be set to less than 0.5%. The B concentration may also be set to less than 0.4%, less than 0.2%, or less than 0.1%.
[0080] The coating weight of the plating layer 12 is not limited, but is preferably 10 g / m2 per side in order to improve corrosion resistance. 2 The adhesion amount can also be set to 20g / m per side. 2 Above, 35g / m 2 Above, 50g / m 2 Above or 70g / m 2 On the other hand, even if the adhesion exceeds 200g / m 2 The corrosion resistance is also saturated, and it becomes economically disadvantageous. Therefore, the amount of adhesion on each side is preferably 200g / m 2 The adhesion amount can also be set to 175g / m 2 Below, 150g / m 2 Below, 125g / m 2 Below or 110g / m 2 the following.
[0081] <Chemical conversion coating>
[0082] [Contains silicon compound, P and F, and Mg, and the average Si concentration of the chemical conversion film is 10 mass % or more]
[0083] The chemical conversion treatment film 13 of the surface-treated steel sheet 1 of the present embodiment is obtained by applying a treatment solution containing a P compound such as a silane coupling agent, a fluoride and a phosphate to a zinc-containing plating layer under specified conditions and drying it. Therefore, the chemical conversion treatment film 13 of the surface-treated steel sheet 1 of the present embodiment contains a silicon compound containing Si, C, and O derived from a silane coupling agent as a film-forming component, and contains P derived from a P compound and F derived from a fluoride as an inhibitor component. In addition, the chemical conversion treatment film 13 contains Mg derived from a Mg compound, etc. When the silicon compound is a film-forming component, the average Si concentration of the chemical conversion treatment film becomes 10% by mass or more. The average Si concentration can also be set to 11% by mass or more, 12% by mass or more, 14% by mass or more, or 16% by mass or more. The upper limit of the average Si concentration is not limited, but the average Si concentration can also be 35% by mass or less. The average Si concentration can also be set to 30% by mass or less, 27% by mass or less, 24% by mass or less, 22% by mass or less, or 20% by mass or less.
[0084] The maximum value of the P concentration obtained by the measurement method described later is preferably 0.01 mass% or more, more preferably 0.02 mass% or more, 0.05 mass% or more, or 0.10 mass% or more. It is not necessary to particularly specify the average P concentration, but the average P concentration may be set to 0.01 mass% or more, 0.05 mass% or more, 0.10 mass% or more, 0.20 mass% or more, 0.50 mass% or more, 0.80 mass% or more, or 1.20 mass% or more. The average P concentration may also be 10.00 mass% or less, 7.00 mass% or less, 5.00 mass% or less, or 3.00 mass% or less.
[0085] The maximum value of the F concentration obtained by the measurement method described later is preferably 0.01 mass% or more, 0.05 mass% or more, and more preferably 0.10 mass% or more. It is not necessary to particularly specify the average F concentration, but the average F concentration may be set to 0.01 mass% or more, 0.05 mass% or more, 0.10 mass% or more, 0.15 mass% or more, or 0.20 mass% or more. The average F concentration may also be 1.10 mass% or less, 1.00 mass% or less, 0.70 mass% or less, 0.50 mass% or less, 0.40 mass% or less, or 0.35 mass% or less.
[0086] The maximum value of the Mg concentration obtained by the measurement method described later is preferably 0.05 mass% or more, and more preferably 0.10 mass% or more. It is not necessary to particularly specify the average Mg concentration, but the average Mg concentration may be set to 0.01 mass% or more, 0.05 mass% or more, 0.10 mass% or more, 0.15 mass% or more, or 0.20 mass% or more. The average Mg concentration may also be 1.00 mass% or less, 0.70 mass% or less, 0.50 mass% or less, 0.40 mass% or less, or 0.35 mass% or less.
[0087] In addition, the chemical conversion coating 13 may contain Zr and V derived from Zr compounds and V compounds as required. The content of Zr and V derived from Zr compounds and V compounds is arbitrary, and the lower limits of the average Zr concentration and the average V concentration are 0%. The average Zr concentration and the average V concentration may also be set to 3.00 mass % or less, 2.00 mass % or less, 1.00 mass % or less, 0.70 mass % or less, or 0.50 mass % or less, respectively.
[0088] Whether the chemical conversion coating contains P, F, Mg, Zr, and V, and the average Si concentration in the chemical conversion coating are determined by the following method.
[0089] A sample of a size that can be inserted into a low-temperature FIB processing device is cut out from a surface-treated steel material formed with a chemical conversion coating, and a test piece with a thickness of 80 to 200 nm is cut out from the sample by a low-temperature FIB (focused ion beam) method. The cross-sectional structure of the cut test piece is observed using a transmission electron microscope (TEM: Transmission Electoron Microscope) at a magnification that allows the entire chemical conversion coating to enter the observation field. In order to determine the constituent elements of each layer, TEM-EDS (energy dispersive X-ray spectroscopy; Energy Dispersive X-ray Spectroscopy) is used to perform quantitative analysis of Si, P, F, Mg, Zr, and V at more than 5 points in the coating. The average value of the Si concentration at each point is used as the average Si concentration of the chemical conversion coating. On the other hand, for P, F, Mg, Zr, and V, if detected at even one point among the respective points (when a value exceeding the detection limit (for example, 0.001 mass % or more or 0.005 mass % or more as a concentration) is obtained), it is determined that the element is contained in the film. However, an apparatus having a detection limit of at least 0.01 mass % or less for P, F, Mg, Zr, and V is used. That is, if there is even one measurement point where the content thereof becomes 0.01 mass % or more, it is determined that the element is definitely contained.
[0090] Whether the chemical conversion coating contains a silicon compound (whether Si exists as a silicon compound) can be confirmed using FT-IR.
[0091] Specifically, a general FT-IR device was used to confirm the presence of 1030 to 1200 cm-1 wavelengths representing siloxane bonds. -1 When there is a peak of absorbance of , it is judged that a silicon compound is contained. As the FT-IR apparatus, for example, the model: Frontier IR manufactured by PERKIN ELMER can be used.
[0092] In FT-IR, measurement conditions are as follows, for example.
[0093] Measurement method: Diffuse reflectance method
[0094] Resolution: 4cm -1
[0095] Cumulative times: 128 times
[0096] Measuring atmosphere: Atmosphere
[0097] [An F-Mg concentrated layer having a Mg concentration of 1.50 mass % to 40.00 mass % and a F concentration of 0.50 mass % to 5.00 mass % in a region in contact with the interface between the film and the plated layer]
[0098] The present inventors have studied a method for suppressing the generation of white rust in an environment in contact with running water and an environment in which condensation occurs, based on a Mg-containing zinc-plated steel sheet subjected to a chemical conversion treatment mainly using an organic silicon compound. As a result, it has been found that the white rust resistance in an environment in contact with running water (running water environment) can be improved by forming a layer (F-Mg concentrated layer) having a Mg concentration of 1.50 mass % to 40.00 mass % and a F concentration of 0.50 mass % to 5.00 mass % in a region of the chemical conversion film in contact with the interface between the plating layer and the chemical conversion film.
[0099] Although the mechanism of the improvement of white rust resistance by the F-Mg concentrated layer is not clear, it is considered that the F-Mg concentrated layer in which F and Mg are concentrated is an amorphous layer containing a Mg-F composite salt, and the white rust resistance is considered to be improved due to the high barrier property of the amorphous layer.
[0100] In the past, it was shown that a Zn-F composite salt or an Al-F composite salt is formed near the interface. However, as a result of the research conducted by the inventors, the test piece after the corrosion resistance test in the flowing water environment was observed with a transmission electron microscope (TEM), and it was confirmed that the Zn-F composite salt and the Al-F composite salt disappeared. On the other hand, the Mg-F composite salt was also confirmed to remain after the corrosion resistance test in the flowing water environment. That is, the Mg-F composite salt maintains the layer, that is, maintains the barrier effect, for a longer time than the Zn-F composite salt or the Al-F composite salt even in the flowing water environment. Therefore, it is believed that the improvement of the white rust resistance in the flowing water environment is insufficient when the F-Mg concentrated layer is not formed.
[0101] The above-mentioned effect cannot be obtained in a layer having a Mg concentration of less than 1.50 mass % or a layer having a Mg concentration of less than 0.50 mass %.
[0102] Even if F and Mg are concentrated, in a layer in which the Mg concentration exceeds 40.0 mass % or the F concentration exceeds 5.00 mass %, the blackening resistance is reduced.
[0103] Therefore, in the present embodiment, a layer having a Mg concentration of 1.50 mass % to 40.00 mass % and a F concentration of 0.50 mass % to 5.00 mass % is set as a F—Mg concentrated layer.
[0104] In the present embodiment, the presence of the F—Mg concentrated layer means that the average thickness of the F—Mg concentrated layer measured at 10 locations by a measuring method described later is 1.0 nm or more.
[0105] The thickness of the F-Mg concentrated layer (the thickness from the interface between the plated layer and the chemical conversion treatment film) is preferably 5.0 nm or more and 100.0 nm or less on average.
[0106] When the thickness of the F-Mg concentrated layer is 5.0 nm or more, the improvement of white rust resistance becomes remarkable. Therefore, the thickness of the F-Mg concentrated layer is preferably 1.5 nm or more, 2.0 nm or more, 3.0 nm or more, or 5.0 nm or more, and more preferably 10.0 nm or more, 20.0 nm or more, 40.0 nm or more, or 60.0 nm or more.
[0107] On the other hand, the F-Mg concentrated layer is hard. If the thickness of the F-Mg concentrated layer is thick, when the surface-treated steel sheet is processed, the amorphous layer sometimes becomes the starting point and the chemical conversion treatment film peels off. In this case, the corrosion resistance of the processed part may be reduced. Therefore, from the viewpoint of suppressing the film peeling of the processed part, it is preferred to set the thickness of the F-Mg concentrated layer to 200.0nm or less, 150.0nm or less, or 120.0nm or less. In the case of obtaining a more excellent corrosion resistance of the processed part, it is preferred to set the thickness of the F-Mg concentrated layer to 100.0nm or less.
[0108] [In the region other than the F-Mg concentrated layer, the average Mg concentration is lower than 0.50 mass %, and the average F concentration is lower than 0.50 mass %]
[0109] In the surface treated steel sheet 1 of the present embodiment, if the average Mg concentration in the region other than the F-Mg concentrated layer is 0.50 mass % or more, the blackening resistance is reduced. Therefore, in order to ensure sufficient (same as or higher than the conventional) blackening resistance, the Mg concentration in the region other than the F-Mg concentrated layer is set to less than 0.50 mass %. If necessary, the Mg concentration in the region other than the F-Mg concentrated layer may be set to 0.45 mass % or less, 0.40 mass % or less, or 0.35 mass % or less.
[0110] Furthermore, the inventors have found out from the results of their studies that, in the surface-treated steel sheet 1 of the present embodiment, if the average F concentration in the region other than the F-Mg concentrated layer is 0.50 mass % or more, the white rust resistance in an environment where condensation occurs is reduced. Therefore, in the surface-treated steel sheet 1 of the present embodiment, the average F concentration in the region other than the F-Mg concentrated layer is set to less than 0.50 mass %. If necessary, the F concentration in the region other than the F-Mg concentrated layer may be set to 0.45 mass % or less, 0.40 mass % or less, or 0.35 mass % or less.
[0111] The thickness of the F-Mg concentrated layer (the thickness from the interface between the plated layer and the chemical conversion treatment film) was determined by the following method.
[0112] A sample of a size that can be inserted into a low-temperature FIB processing device is cut out from a surface-treated steel material formed with a chemical conversion coating, and a test piece with a thickness of 80 to 200 nm is cut out from the sample by the low-temperature FIB (Focused Ion Beam) method. The cross-sectional structure of the cut test piece is observed using a transmission electron microscope (TEM: Transmission Electron Microscope) at a magnification such that the entire chemical conversion coating enters the observation field.
[0113] Based on the observed image, the interface between the coating and the chemical conversion coating (chemical conversion coating) was visually determined, and the concentrations of F and Mg were measured by line analysis in parallel with the thickness direction of the coating. At this time, the starting point of the analysis was set to a position 100 nm from the interface between the coating and the chemical conversion coating to the steel sheet side, and the end point was set to the surface of the chemical conversion coating. In addition, the measurement interval of the line analysis was set to 1.0 nm.
[0114] As a result of the measurement, the range where the Mg concentration was 1.50 mass % or more and 40.00 mass % or less and the F concentration was 0.50 mass % or more and 5.00 mass % or less was determined to be the F-Mg concentrated layer, and this thickness was set as the thickness of the F-Mg concentrated layer. However, the measurement was performed at 10 points at intervals of 100 nm in a direction perpendicular to the thickness direction from an arbitrary point, and the average of the results was set as the thickness of the F-Mg concentrated layer.
[0115] The average Mg concentration and the average F concentration in the region other than the F—Mg concentrated layer were determined by the following method.
[0116] When measuring the thickness of the above-mentioned F-Mg concentrated layer, the point in the F-Mg concentrated layer farthest from the interface between the plating layer and the chemical conversion treatment film (the F-Mg concentrated layer is a part of the chemical conversion treatment film, and is formed in the part of the chemical conversion treatment film adjacent to the plating layer. Therefore, the point in the F-Mg concentrated layer farthest from the interface between the plating layer and the chemical conversion treatment film is the point in the F-Mg concentrated layer closest to the surface of the chemical conversion treatment film.) is set as the starting point, and line analysis is performed at a spacing of 1.0 nm to the surface of the chemical conversion treatment film to measure the Mg concentration and the F concentration, and their average values are set as the average Mg concentration and the average F concentration, respectively.
[0117] The thickness of the chemical conversion film 13 including the F—Mg concentrated layer is preferably 0.02 to 2.0 μm, more preferably 0.2 to 2.0 μm.
[0118] Regarding the thickness of the chemical conversion coating, the boundary between the plating layer and the chemical conversion coating can be easily identified due to the difference in contrast during the above-mentioned TEM observation, so the distance from the boundary to the surface of the chemical conversion coating is measured and set as the thickness. When measuring, 10 points are measured at intervals of 100 nm in a direction perpendicular to the thickness direction from an arbitrary point, and the average of the measurement results is set as the thickness of the chemical conversion coating.
[0119] <Manufacturing method>
[0120] Next, a preferred method for producing the surface-treated steel sheet according to the present embodiment will be described.
[0121] The surface-treated steel sheet of the present embodiment can obtain the effects as long as it has the above-mentioned characteristics regardless of the manufacturing method, but the following manufacturing method is preferred because it can be stably manufactured.
[0122] That is, the surface-treated steel sheet according to the present embodiment can be produced by a production method including the following steps.
[0123] (I) a plating step of forming a plating layer on the surface by immersing the steel sheet in a plating bath containing Zn and Mg, scooping it out, and water-cooling it;
[0124] (II) a step of applying a chemical conversion treatment solution containing a silane coupling agent, a fluoride, acetylacetone (acetylacetonate), a P compound, and Mg to the steel sheet having the plated layer;
[0125] (III) A heating step of heating the steel sheet coated with the chemical conversion treatment liquid to form a film (chemical conversion treatment film) containing a silicon compound, P, F, and Mg.
[0126] Hereinafter, preferred conditions for each step will be described.
[0127] [Plating process]
[0128] In the plating step, the steel sheet is immersed in a plating bath containing Zn and Mg, taken out, and water-cooled to form a plating layer on the surface.
[0129] In the past, as the Mg-containing zinc-based plating layer, a zinc-based plating layer having a Mg concentration of less than 10% by mass on the plating surface can be used. In contrast, in the present embodiment, the Mg concentration of the plating surface in the stage of chemical conversion treatment is set to 20% by mass or more. By setting the Mg concentration of the plating surface to 20% by mass or more, the supply of Mg to the interface can be promoted. In this case, by applying a predetermined chemical conversion treatment solution and heating as described below, an F-Mg concentrated layer can be formed on the chemical conversion treatment film.
[0130] On the other hand, if the Mg concentration of the plated surface exceeds 60 mass %, the Mg concentration of the layer formed at the interface becomes excessive. Therefore, the Mg concentration of the plated surface is set to 60 mass % or less.
[0131] The Mg concentration of the plated surface after the plating process (before the chemical conversion treatment) can be controlled by the water cooling conditions after the steel sheet is taken out of the plating bath. Specifically, during water cooling, by adjusting the pH of the cooling water to 9.5 or more and controlling the temperature of the steel sheet immediately before contact with the cooling water to 170°C or less, the Mg concentration of the plated surface can be set to 20 mass % or more and 60 mass % or less.
[0132] The reason why the Mg concentration on the plated surface can be adjusted by controlling the water cooling conditions is explained. In Mg-containing zinc-plated steel sheets, Mg with high affinity for oxygen is concentrated in the surface layer of the plated layer with a thickness of about several nm just after the plated layer solidifies. However, this Mg is extremely unstable and easily dissolves in water during water cooling after plating, and the Mg concentration on the surface becomes the same as the Mg concentration in the plated layer. On the other hand, by controlling the water cooling to the above range, the dissolution of Mg can be suppressed, and the Mg concentration on the surface of the plated layer can be set to 20 to 60% by mass.
[0133] The mechanism for suppressing the dissolution of Mg is not clear, but it is believed that by adjusting the pH to 9.5 or above, Mg is close to the passive state, and the reaction of Mg with water is suppressed by the low temperature of the steel sheet. When the pH is lower than 9.5, the Mg concentration on the plated surface becomes lower than 20% by mass. In addition, when the temperature of the steel sheet just before contacting with cooling water exceeds 170°C, the Mg concentration on the plated surface becomes lower than 20% by mass.
[0134] On the other hand, when the pH exceeds 11.0, the appearance of the plated layer deteriorates. In this case, the appearance after the chemical conversion treatment film is formed also deteriorates, so the pH is preferably 11.0 or less.
[0135] In the stage after the plating step and before the chemical conversion treatment, the thickness of the Mg-rich layer having a Mg concentration of 20 mass % or more and 60 mass % or less is preferably set to 3.0 to 100 nm. By setting the thickness of the Mg-rich layer to 3.0 to 100 nm, it is advantageous to set the thickness of the F-Mg-rich layer after the chemical conversion treatment to 5.0 to 100.0 nm.
[0136] When the thickness of the Mg concentrated layer is set to 3.0 to 100 nm, the temperature of the steel sheet immediately before contact with cooling water is preferably set to 120° C. or higher and 150° C. or lower.
[0137] The thickness of the Mg-concentrated layer having a Mg concentration of 20 mass % or more and 60 mass % or less can be determined by the following method.
[0138] A sample of a size that can be inserted into a low-temperature FIB processing device is cut out from the plated steel plate before chemical conversion treatment, and a test piece with a thickness of 80 to 200 nm is cut out from the sample by the low-temperature FIB (Focused Ion Beam) method. The cross-sectional structure of the cut test piece is observed using a transmission electron microscope (TEM: Transmission Electoron Microscope) at a magnification such that the entire thickness direction of the coating enters the observation field.
[0139] Based on the observed image, the interface between the coating and the base steel sheet was determined, and the concentration of Mg was measured by line analysis parallel to the thickness direction of the coating. At this time, the starting point of the analysis was set to a position 100 nm from the interface between the coating and the steel sheet to the steel sheet side, and the end point was set to the surface of the coating. In addition, the measurement interval of the line analysis was set to 1 nm.
[0140] As a result of the measurement, the range of Mg concentration of 20 mass % or more and 60 mass % or less was judged as the Mg concentrated layer, and the thickness was set as the thickness of the Mg concentrated layer. However, the measurement was performed at 10 points at intervals of 100 nm in a direction perpendicular to the thickness direction from an arbitrary point, and the average was set as the thickness of the Mg concentrated layer.
[0141] When the thickness of the concentrated layer determined by TEM is 5 nm or less during measurement, it is preferred to use a TEM having a spherical aberration correction function from the viewpoint of spatial resolution.
[0142] The steel sheet to be subjected to the plating step and its manufacturing method are not limited. As the steel sheet immersed in the plating bath, for example, a hot-rolled mild steel sheet or hot-rolled steel sheet described in JIS G3131:2018 or JIS G3113:2018, or a cold-rolled steel sheet described in JIS G3141:2017 can be used.
[0143] The composition of the plating bath may be adjusted according to the chemical composition of the desired plating layer.
[0144] After the steel sheet is taken out of the plating bath, the amount of plating applied can be adjusted by wiping it.
[0145] To adjust the pH of the cooling water, various known pH adjusters may be used.
[0146] [Coating process]
[0147] In the coating step, a chemical conversion treatment liquid is applied to the steel sheet (plated steel sheet) on which the coating layer is formed. As the chemical conversion treatment liquid, a treatment liquid containing a silane coupling agent, a fluoride, acetylacetone (acetylacetonate), a P compound, and a Mg compound can be used. The chemical conversion treatment liquid may also contain a Zr compound and a V compound.
[0148] In the coating step, the coating method of the surface treatment metal agent is not limited, and the coating can be performed using, for example, a roll coater, a bar coater, a sprayer, or the like.
[0149] The silane coupling agent is included as a film-forming component. For example, a Si compound obtained by mixing a silane coupling agent (A) containing one amino group in the molecule and a silane coupling agent (B) containing one glycidyl group in the molecule at a solid content concentration ratio (A) / (B) of 0.5 to 1.7 can be used.
[0150] The P (phosphorus) compound contained in the chemical conversion treatment liquid remains in the chemical conversion treatment film as an inhibitor component P. The corrosion resistance of the chemical conversion treatment film is improved by the P as the inhibitor component.
[0151] Regarding the amount of the P compound (T), the solid content mass ratio of Si derived from the organosilicon compound (S) to P derived from the phosphorus compound (T) [(Ts) / (Ss)] is preferably set to 0.15 to 0.31. If the solid content mass ratio of Si derived from the organosilicon compound (S) to P derived from the P compound (T) [(Ts) / (Ss)] is less than 0.15, the effect of the P compound (T) as a dissolution inhibitor cannot be obtained, which is not preferred. On the other hand, if [(Ts) / (Ss)] exceeds 0.31, the water solubility of the film becomes significant, which is not preferred.
[0152] In this embodiment, the P compound contained in the chemical conversion treatment liquid is not particularly limited, but examples thereof include phosphoric acid, ammonium phosphate, potassium phosphate, sodium phosphate, etc. Among them, phosphoric acid is more preferred. When phosphoric acid is used, better corrosion resistance can be obtained.
[0153] The fluoride in the chemical conversion treatment liquid reacts with the Mg of the plated layer to form an F-Mg concentrated layer. Therefore, in the case of obtaining the surface-treated steel sheet of the present embodiment, the chemical conversion treatment liquid contains fluoride (fluorine compound).
[0154] Regarding the amount of fluoride (U) incorporated, the amount of fluoride contained in the chemical conversion treatment liquid is preferably such that the mass ratio [(Us) / (Xs)] of the solid component (X) contained in the chemical conversion treatment liquid to F as a fluoride source is set to 0.02 to 0.70. When [(Us) / (Xs)] is less than 0.02, there is a concern that the F concentration near the interface becomes less than 0.5% by mass, and the predetermined F-Mg layer is not formed. On the other hand, when [(Us) / (Xs)] exceeds 0.70, there is a concern that the F concentration in the portion other than the F-Mg concentrated layer becomes more than 0.50% by mass.
[0155] As the fluoride contained in the chemical conversion treatment liquid, compounds such as hydrofluoric acid HF, fluoroboric acid BF4H, fluorosilicic acid H2SiF6, fluorozirconic acid H2ZrF6, fluorotitanic acid H2TiF6, ammonium titanium fluoride (NH4)2TiF6, and ammonium zirconium fluoride (NH4)2ZrF6 can be exemplified. The compound can also be a combination of one or more kinds. Among them, hydrofluoric acid is more preferred. When hydrofluoric acid is used, more excellent corrosion resistance and coating properties can be obtained.
[0156] Mg contained in the chemical conversion treatment solution contributes to the formation of the F-Mg concentrated layer. The reason for this is not clear, but it is presumed that the formation of the F-Mg concentrated layer starts near the interface with the plating layer.
[0157] When the chemical conversion treatment liquid does not contain Mg, even if Mg is contained in the plating layer, a F—Mg concentrated layer is not sufficiently formed at the interface, and a sufficient effect of improving white rust resistance cannot be obtained.
[0158] Examples of the Mg compound contained in the chemical conversion treatment liquid include magnesium fluoride, magnesium nitrate, magnesium sulfate, magnesium chloride, and magnesium acetate.
[0159] When Mg is contained in the chemical conversion treatment liquid in the form of a Mg compound, the amount of the Mg compound contained in the chemical conversion treatment liquid is preferably set to a mass ratio [(Vs) / (Xs)] of Mg of the solid component (X) contained in the chemical conversion treatment liquid to that of the Mg compound to be 0.05 to 0.60. When [(Vs) / (Xs)] is less than 0.05, there is a concern that the F concentration near the interface becomes less than 0.5% by mass, and a predetermined F-Mg concentrated layer is not formed. On the other hand, when [(Vs) / (Xs)] exceeds 0.60, there is a concern that the Mg concentration in the portion other than the F-Mg concentrated layer becomes more than 0.5% by mass.
[0160] Acetylacetone (acetylacetonate) contained in the chemical conversion treatment solution contributes to the stabilization of the Mg compound and inhibits the reaction of the Mg compound with the components in the treatment solution during storage of the treatment solution. If the chemical conversion treatment solution does not contain acetylacetone, a sufficient F-Mg concentration layer is not formed.
[0161] Regarding the amount of acetylacetone (W) to be added, the molar ratio of acetylacetone (W) to the Mg compound (V) [(W mol) / (V mol)] is preferably set to 1.0 to 10.0. If the molar ratio of acetylacetone (W) to the Mg compound (V) [(W mol) / (V mol)] is less than 1.0, the F concentration near the interface may be less than 0.5% by mass, and a predetermined F-Mg concentrated layer may not be formed. On the other hand, if [(W mol) / (V mol)] exceeds 10.0, the stabilizing effect of the Mg compound is saturated, and the economic efficiency is poor.
[0162] When the chemical conversion treatment liquid contains a Zr compound, ammonium zirconium carbonate, hexafluorozirconic acid, ammonium hexafluorozirconate, and the like can be exemplified.
[0163] In addition, in the case of including a V compound, examples include vanadium pentoxide V2O5, metavanadic acid HVO3, ammonium metavanadate, sodium metavanadate, vanadium oxytrichloride VOCl3, vanadium trioxide V2O3, vanadium dioxide VO2, vanadium oxysulfate VOSO4, vanadium acetylacetonate VO(OC(=CH2)CH2COCH3))2, vanadium acetylacetonate V(OC(=CH2)CH2COCH3))3, vanadium trichloride VCl3, vanadophosphomolybdic acid, etc. In addition, a vanadium compound obtained by reducing a pentavalent vanadium compound to a tetravalent to divalent vanadium compound with an organic compound having at least one functional group selected from the group consisting of a hydroxyl group, a carbonyl group, a carboxyl group, a primary to tertiary amino group, an amide group, a phosphoric acid group, and a phosphonic acid group may also be used.
[0164] [Heating process]
[0165] In the heating step, the steel sheet coated with the chemical conversion treatment liquid is heated to be dried and baked, thereby forming a chemical conversion treatment film on the surface of the coating layer.
[0166] Regarding the heating temperature (drying temperature), if the maximum temperature reached is lower than 60°C, the solvent of the surface treatment metal agent is not completely volatilized, so it is not preferred. On the other hand, if the maximum temperature reached exceeds 200°C, the solvent drying effect brought about by heating is saturated, which is not economical and is therefore not preferred. Therefore, the maximum temperature reached is preferably 60 to 200°C, and more preferably 80 to 150°C.
[0167] In the heating step, the heating method is not limited, and for example, heating and drying can be performed using IH, a hot air furnace, or the like.
[0168] Example
[0169] A cold rolled steel sheet (plated original sheet) having a thickness of 0.8 mm satisfying JIS G3141:2017 was immersed in a plating bath having a composition shown in Table 1, and after being scooped up, the adhesion amount was adjusted to that shown in Table 8 by wiping with N2 gas. Thereafter, the plated steel sheets (O1 to O31) were obtained by water cooling under the conditions of Table 8 using cooling water to which the pH adjusting agent shown in Table 2 was added and adjusted. In Table 1, for example, Zn-6.0%Al-3.0%Mg indicates a composition containing 6.0 mass% Al, 3.0 mass% Mg, and the remainder containing Zn and impurities.
[0170] The appearance of the obtained plated steel sheet was evaluated visually. Specifically, if the plated steel sheet was partially or completely whitened, it was judged as "F (Fair)" (although it can be applied to parts that do not require appearance or used for repair, it is difficult to use it directly for parts that require appearance, which is not preferred). On the other hand, if the plated steel sheet was not confirmed, it was judged as "G (Good)" (excellent appearance).
[0171] Furthermore, the thickness of a region having a Mg concentration of 20 to 60 mass % from the surface layer of the plated layer was measured.
[0172] For the obtained plated steel sheets, water-based surface treatment metal agents ST1 to ST21 were prepared by mixing the silicon compounds (silane coupling agents), P compounds, fluorides, Mg compounds, and acetylacetone shown in Tables 3 to 7 at the ratios shown in Table 9.
[0173] The surface treatment metal agents of ST1 to ST21 are applied to the plated steel sheets O1 to O31 by a roll coater and dried to form a film. At this time, the amount of film adhesion, the combination of the plated steel sheet and the surface treatment metal agent are set as shown in Tables 10-1 to 10-4. Drying is heating (steel sheet temperature reaches) to the drying plate temperature of Tables 10-1 to 10-4, and maintaining for 2 seconds to form a film.
[0174] Thus, surface-treated steel sheets Nos. 1 to 120 were manufactured.
[0175] The thickness of the chemical conversion coating, the Si concentration, P concentration, F concentration, Mg concentration, Zr concentration, and V concentration of the chemical conversion coating were measured according to the above-mentioned method. The results are shown in Tables 11-1 to 11-4. In the table, "-" in the columns of Zr concentration and V concentration means that no concentration of 0.001 mass % or more was detected in any measurement.
[0176] Although not shown in the table, the results of FT-IR measurement in all examples showed that Si was present as a silicon compound.
[0177] In addition, the thickness of the F-Mg concentrated layer of the chemical conversion coating was measured according to the above method. The results are shown in Tables 11-1 to 11-4. At this time, the averages of the F concentration and Mg concentration at the position of 1.0 nm were as shown in Tables 11-1 to 11-4.
[0178] Furthermore, the F concentration and the Mg concentration in the portion other than the F-Mg layer were measured according to the above-mentioned procedure.
[0179] In addition, the obtained surface treated steel sheets were evaluated for corrosion resistance (SST), white rust resistance in an environment in contact with running water, corrosion resistance in a condensation environment, Erichsen processing corrosion resistance, blackening resistance, and appearance according to the following procedures. The results are shown in Tables 12-1 to 12-4.
[0180] "Corrosion resistance (SST)"
[0181] Flat test pieces (100 mm×100 mm) were prepared, and each test piece was subjected to a salt spray test in accordance with JIS Z2371:2015, and the occurrence of white rust on the surface after 120 hours (the ratio of the area of white rust to the area of the test piece) was evaluated.
[0182] <Evaluation Criteria>
[0183] EX (Excellent): Rust generation is less than 5% of the total area
[0184] G (Good): Rust occurs on 5% or more and less than 10% of the total area
[0185] P (Poor): Rust accounts for more than 10% of the total area
[0186] "White rust resistance in environments with running water"
[0187] A flat test piece (100 mm × 100 mm) was made from the obtained surface-treated steel plate, and the test piece was fixed with the test surface at an angle of 45 degrees relative to the vertical line. After that, a salt solution with a salt concentration of 50 g / L and a pH of 6.5 to 7.2 was dripped onto each test piece. The salt solution was dripped from a hose with an inner diameter of 3 mm. The front end of the hose was set to a position 20 mm away from the center of the upper end of the test piece to the lower end, and the distance between the test piece and the front end of the hose was set to 20 mm. The dripping speed was set to 10 ml / s.
[0188] The dripping test was carried out in the above manner, and the occurrence of white rust on the surface after 120 hours was evaluated. The part where the salt water was dripped directly from the hose (the area of 20 mm φ with the above target position as the center) was called the dripping part, and the flow path of the salt water flowing from the dripping part was called the water flow part.
[0189] Evaluation was performed according to the following evaluation criteria, and when it was Ex or G, it was judged that the white rust resistance was excellent.
[0190] <Evaluation Criteria>
[0191] Ex (Exellent): No white rust
[0192] G (Good): White rust is generated in the dripping part, and no white rust is generated in the water flow part
[0193] P (Poor): White rust occurs in both the dripping part and the water flow part
[0194] "Corrosion resistance in condensation environments"
[0195] A flat test piece (100 mm × 100 mm) was prepared from the obtained surface treated steel plate, and 5 ml of the salt water used was dripped into the center of the test piece by spraying the neutral salt water described in JIS Z 2371: 2015. The test piece after the salt water was dripped was stored at 50°C-98% RH for 240 hours, and the generation of white rust was evaluated. If it is G, it is judged that the corrosion resistance in the condensation environment is excellent.
[0196] <Evaluation Criteria>
[0197] G(Good): No white rust
[0198] P (Poor): White rust occurs
[0199] "Erickson processing part corrosion resistance"
[0200] A flat test piece (50 mm×50 mm) was prepared from the obtained surface-treated steel sheet, and after being subjected to an Erichsen test (extruded to 7 mm), a salt spray test in accordance with JIS Z 2371:2015 was performed for 120 hours to observe the occurrence of white rust.
[0201] If it is Ex or G, it is judged that the Erichsen processed portion corrosion resistance is excellent.
[0202] <Evaluation Criteria>
[0203] Ex (Exellent): Rust generation is less than 10% of the processed area
[0204] G (Good): Rust is 10% or more and less than 30% of the processed area
[0205] P (Poor): Rust occurs on more than 30% of the processed area
[0206] "Darkness resistance"
[0207] A test plate (50 mm x 50 mm) was prepared from the obtained surface treated steel plate, and the test plate was kept in a wet box at 70°C and 80% relative humidity for 6 days, then taken out and the blackening condition of the test plate was visually determined.
[0208] The evaluation criteria were set as follows: G was judged as acceptable, and Ex was judged as particularly excellent in blackening resistance.
[0209] Ex (Exellent): The area ratio of black spots is less than 1%
[0210] G (Good): The area ratio of the blackened part is 1% or more and less than 25%
[0211] P (Poor): The area ratio of the blackened part is 25% or more
[0212] "Appearance"
[0213] A test plate (300 mm×300 mm) was prepared from the obtained surface-treated steel plate, and the appearance of the test plate was visually evaluated.
[0214] The evaluation criteria were set as follows, and a value of G was considered to be excellent in appearance.
[0215] G(Good): No discoloration
[0216] P (Poor): partial or entire surface of the test plate changes color
[0217] Table 1
[0218] Plating composition A Zn-6.0%AI-3.0%Mg B Zn-11.0%Al-3.0%Mg-0.2%Si C Zn-16.0%AI-6.0%Mg-0.2%Si D Zn-19.0%AI-6.0%Mg-1.5%Sn-0.5%Ca-0.2%Si E Zn-24.0%AI-12.0%Mg-0.5%Ca-1.2%Si
[0219] Table 2
[0220] name Q1 Potassium carbonate Q2 Sodium bicarbonate Q3 Methylamine Q4 Dimethylamine
[0221] Table 3
[0222] name A1 3-Aminopropyltrimethoxysilane A2 3-Aminopropyltriethoxysilane B1 3-Glycidoxypropyltrimethoxysilane B2 3-Glycidoxypropyltriethoxysilane
[0223] Table 4
[0224] name T1 Phosphoric acid T2 Ammonium phosphate
[0225] Table 5
[0226] name U 1 Hydrofluoric acid U2 Fluorosilicic acid U3 Fluotitanic acid U4 Ammonium Titanium Fluoride U5 Fluorozirconic acid U6 Ammonium zirconium fluoride
[0227] Table 6
[0228] name V1 Magnesium fluoride V2 Magnesium Nitrate V3 Magnesium sulfate V4 Magnesium chloride V5 Magnesium acetate
[0229] Table 7
[0230] name W1 Acetylacetone W2 Nickel acetylacetonate W3 Manganese acetylacetonate W4 Zinc acetylacetonate W5 Vanadyl acetylacetonate
[0231]
[0232]
[0233]
[0234]
[0235]
[0236]
[0237] Table 11-1
[0238]
[0239] Table 11-2
[0240]
[0241] Table 11-3
[0242]
[0243] Table 11-4
[0244]
[0245] Table 12-1
[0246]
[0247] Table 12-2
[0248]
[0249] Table 12-3
[0250]
[0251] Table 12-4
[0252]
[0253] As can be seen from Tables 1 to 12-4, in the examples (Inventive Examples Nos. 1 to 30, 47 to 54, and 97 to 104) in which a predetermined plating layer and a chemical conversion coating are provided on a steel material, the chemical conversion coating has an F-Mg concentrated layer having an Mg concentration of 1.50 mass% to 40.00 mass% and an F concentration of 0.50 mass% to 5.00 mass% in a region in contact with the interface between the chemical conversion coating and the plating layer, and the average Mg concentration in the region other than the F-Mg concentrated layer in the chemical conversion coating is less than 0.50 mass% and the average F concentration is less than 0.50 mass%, the blackening resistance is good, and the generation of white rust is suppressed in both an environment such as contact with running water and an environment such as condensation.
[0254] However, among them, although No. 1 to No. 30 were excellent in appearance, No. 47 to 54 and No. 97 to 104 had inferior appearance of the plating layer of the plated steel sheet, and therefore inferior appearance of the surface treated steel sheet.
[0255] On the other hand, in the comparative examples No. 31 to No. 46, No. 55 to No. 86, and No. 95 to No. 120, the predetermined F-Mg concentrated layer was not obtained, the appearance and blackening resistance were inferior, and / or white rust was generated in one or both of an environment such as contact with running water and an environment such as condensation.
[0256] Industrial Applicability
[0257] According to the present invention, a surface-treated steel sheet capable of suppressing the generation of white rust in any of an environment such as contact with running water and an environment such as condensation can be provided. The surface-treated steel sheet can be applied to steel sheets for civil engineering / construction purposes used in an environment such as contact with running water or an environment such as condensation, and has high industrial applicability.
[0258] Explanation of symbols
[0259] 1. Surface treated steel plate
[0260] 11 Base steel plate
[0261] 12 Plating
[0262] 13 Chemical conversion treatment film
[0263] 14F-Mg Concentrated Layer
Claims
1. A surface treated steel plate, comprising: Base steel plate; a plating layer formed on the base steel sheet, the plating layer containing 50 mass % or more of Zn and 0.3 mass % or more of Mg; and a chemical conversion coating formed on the plated layer, The chemical conversion treatment film comprises a silicon compound, P, F, and Mg, The average Si concentration of the chemical conversion treatment film is 10 mass % or more, The chemical conversion coating has an F-Mg concentrated layer in a region in contact with an interface between the chemical conversion coating and the plating layer, wherein the F-Mg concentrated layer has a Mg concentration of 1.50 mass % or more and 40.00 mass % or less, and a F concentration of 0.50 mass % or more and 5.00 mass % or less, The thickness of the F-Mg concentrated layer is greater than 1.0 nm. In the region other than the F—Mg concentrated layer in the chemical conversion coating, the average Mg concentration is lower than 0.50 mass %, and the average F concentration is lower than 0.50 mass %.
2. The surface-treated steel sheet according to claim 1, wherein: In the chemical conversion coating, the thickness of the F-Mg concentrated layer is 5.0 nm or more and 100.0 nm or less.
3. The surface-treated steel sheet according to claim 1 or 2, wherein: The chemical composition of the coating is as follows in mass %: Al: 4.0% or more and less than 25.0%, Mg: 0.3% or more and less than 12.5%, Sn: 0% or more and 20% or less, Bi: 0% or more and less than 5.0%, In: 0% or more and less than 2.0%, Ca: 0% or more and 3.0% or less, Y: 0% or more and 0.5% or less, La: 0% or more and less than 0.5%, Ce: 0% or more and less than 0.5%, Si: 0% or more and less than 2.5%, Cr: 0% or more and less than 0.25%, Ti: 0% or more and less than 0.25%, Ni: 0% or more and less than 0.25%, Co: 0% or more and less than 0.25%, V: 0% or more and less than 0.25%, Nb: 0% or more and less than 0.25%, Cu: 0% or more and less than 0.25%, Mn: 0% or more and less than 0.25%, Fe: 0% or more and less than 5.0%, Sr: 0% or more and less than 0.5%, Sb: 0% or more and less than 0.5%, Pb: 0% or more and less than 0.5%, B: 0% or more and less than 0.5%, and the remainder: Zn and impurities.
Citation Information
Patent Citations
Hot-dip zinc alloy plated steel sheet having excellent corrosion resistance
JP2007023309A
Connector
JP2022032606A
Chemical conversion treatment solution and chemically converted steel sheet
CN105723016A
Surface-treated steel plate
CN111788335A